1993
DOI: 10.1139/z93-210
|View full text |Cite
|
Sign up to set email alerts
|

Surface and underwater observations of cooperatively feeding killer whales in northern Norway

Abstract: Killer whales (Orcinus orca) feeding on herring (Clupea harengus) were observed both from the surface and underwater. We refer to one of the feeding techniques used by killer whales as the carousel method, whereby whales cooperatively herded herring into a tight ball close to the surface. During herding and feeding, whales swam around and under a school of herring, performing much lobtailing and porpoising. When the herring were gathered into a tight ball whales often swam with the white underside of their bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(210 citation statements)
references
References 11 publications
11
198
0
1
Order By: Relevance
“…They are characterized by stable social groups, populationspecific foraging strategies and vocal repertoires that are likely to be transmitted through learning. Their feeding behaviors include hunting fishes, cephalopods, sea turtles, sea birds, mustelids, pinnipeds and cetaceans (e.g., Martinez & Klinghammer, 1970;Christensen, 1978;Smith et al, 1981;Hoelzel, 1991;Jefferson et al, 1991;Baird et al, 1992;Similä & Ugarte, 1993;Matkin & Saulitis, 1994;Baird & Dill, 1995;Baird & Dill, 1996;Fertl et al, 1996;Similä et al, 1996;Ford et al, 1998;Baird & Whitehead, 2000;Ford & Ellis, 2006;Simon et al, 2006). The diversity of hunting strategies parallels the diversity of prey on which they feed.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 99%
See 2 more Smart Citations
“…They are characterized by stable social groups, populationspecific foraging strategies and vocal repertoires that are likely to be transmitted through learning. Their feeding behaviors include hunting fishes, cephalopods, sea turtles, sea birds, mustelids, pinnipeds and cetaceans (e.g., Martinez & Klinghammer, 1970;Christensen, 1978;Smith et al, 1981;Hoelzel, 1991;Jefferson et al, 1991;Baird et al, 1992;Similä & Ugarte, 1993;Matkin & Saulitis, 1994;Baird & Dill, 1995;Baird & Dill, 1996;Fertl et al, 1996;Similä et al, 1996;Ford et al, 1998;Baird & Whitehead, 2000;Ford & Ellis, 2006;Simon et al, 2006). The diversity of hunting strategies parallels the diversity of prey on which they feed.…”
Section: Killer Whales As Candidates For Using Culturementioning
confidence: 99%
“…My research took advantage of a few long-term studies of the Norwegian killer whales, including a catalog of almost 600 identified animals, records of pod composition and detailed descriptions of carousel feeding, a group foraging behavior involving corralling and incapacitating herring. In particular, groups of Norwegian (and Icelandic as documented by Simon et al, 2005) killer whales corral herring by circling the fish to trigger their coalescing, ultimately lunging towards and tail-slapping the prey ball to incapacitate the fish before feeding (Christensen, 1978;Similä & Ugarte, 1993;Simon et al, 2005). The primary objectives of my dissertation were to examine the movement behaviors and association patterns of individual free-ranging Norwegian killer whales, whether their movement and vocal behavior related to one another during both foraging and non-foraging contexts, and whether call subunits were assembled syntactically into discrete calls and call sequences.…”
Section: Introduction To Dissertation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…During clear-water conditions in the fall in 1991-1993, an underwater video camera with a view of the upper 15 m of the water column was used to observe feeding behavior (Similä and Ugarte 1993). When possible, the age of herring was determined as adult (≥29 cm) or adolescent (<29 cm) on the basis of length measurements from herring captured during the feeding bouts.…”
Section: Species Identification Of Killer Whale Preymentioning
confidence: 99%
“…Among delphinids, studies on behavioral patterns have mainly been conducted on Orcinus orca (Linnaeus, 1758) (SIMILA & UGARTE 1993, SAULITIS et al 2000, Stenella longirostris (NORRIS & DOHL 1980, SILVA JR et al 2005 and Tursiops truncatus (Montagu, 1821) (WÜRSIG & WÜRSIG 1979, BEARZI et al 1999. Their behavioral patterns seem to resemble those observed for Sotalia guianensis (GEISE et al 1999, ARAÚJO et al 2003, SOUTO et al 2006.…”
mentioning
confidence: 94%